Get the information you need quickly and easily with IDNLearn.com. Ask your questions and receive prompt, detailed answers from our experienced and knowledgeable community members.
Sagot :
To solve the inequality [tex]\( x + 1 \geq x^2 + x \)[/tex], follow these steps:
1. Subtract [tex]\( x + 1 \)[/tex] from both sides of the inequality:
[tex]\[ x + 1 - (x^2 + x) \geq 0 \][/tex]
2. Simplify the expression:
[tex]\[ 1 - x^2 \geq 0 \][/tex]
3. Rewrite the inequality in a more standard form:
[tex]\[ -x^2 + 1 \geq 0 \][/tex]
This can be rewritten as:
[tex]\[ 1 - x^2 \geq 0 \][/tex]
4. Factor the inequality:
Notice that [tex]\(1 - x^2\)[/tex] is a difference of squares, which can be factored as:
[tex]\[ (1 - x)(1 + x) \geq 0 \][/tex]
5. Determine the critical points:
Solve [tex]\( (1 - x)(1 + x) = 0 \)[/tex]:
[tex]\[ 1 - x = 0 \quad \text{or} \quad 1 + x = 0 \][/tex]
This gives the critical points:
[tex]\[ x = 1 \quad \text{and} \quad x = -1 \][/tex]
6. Analyze the intervals defined by the critical points:
The critical points divide the number line into three intervals: [tex]\( (-\infty, -1) \)[/tex], [tex]\( (-1, 1) \)[/tex], and [tex]\( (1, \infty) \)[/tex].
Let's test a point from each interval to determine where the inequality holds:
- For [tex]\( x \in (-\infty, -1) \)[/tex], choose [tex]\( x = -2 \)[/tex]:
[tex]\[ (1 - (-2))(1 + (-2)) = (1 + 2)(1 - 2) = 3 \cdot (-1) = -3 \quad (\text{negative}) \][/tex]
- For [tex]\( x \in (-1, 1) \)[/tex], choose [tex]\( x = 0 \)[/tex]:
[tex]\[ (1 - 0)(1 + 0) = 1 \cdot 1 = 1 \quad (\text{positive}) \][/tex]
- For [tex]\( x \in (1, \infty) \)[/tex], choose [tex]\( x = 2 \)[/tex]:
[tex]\[ (1 - 2)(1 + 2) = (-1) \cdot 3 = -3 \quad (\text{negative}) \][/tex]
Also, check the critical points [tex]\(-1\)[/tex] and [tex]\(1\)[/tex]:
- At [tex]\( x = -1 \)[/tex]:
[tex]\[ (1 - (-1))(1 + (-1)) = (1 + 1)(1 - 1) = 2 \cdot 0 = 0 \quad (\text{zero, which is non-negative}) \][/tex]
- At [tex]\( x = 1 \)[/tex]:
[tex]\[ (1 - 1)(1 + 1) = 0 \cdot 2 = 0 \quad (\text{zero, which is non-negative}) \][/tex]
7. Conclusion:
Based on the test points, we find that the expression [tex]\((1 - x)(1 + x)\)[/tex] is non-negative on the interval [tex]\([-1, 1]\)[/tex].
Therefore, the solution set is:
[tex]\[ x \in [-1, 1] \][/tex]
Thus, the solution to the inequality [tex]\( x + 1 \geq x^2 + x \)[/tex] is:
[tex]\[ [-1, 1] \][/tex]
1. Subtract [tex]\( x + 1 \)[/tex] from both sides of the inequality:
[tex]\[ x + 1 - (x^2 + x) \geq 0 \][/tex]
2. Simplify the expression:
[tex]\[ 1 - x^2 \geq 0 \][/tex]
3. Rewrite the inequality in a more standard form:
[tex]\[ -x^2 + 1 \geq 0 \][/tex]
This can be rewritten as:
[tex]\[ 1 - x^2 \geq 0 \][/tex]
4. Factor the inequality:
Notice that [tex]\(1 - x^2\)[/tex] is a difference of squares, which can be factored as:
[tex]\[ (1 - x)(1 + x) \geq 0 \][/tex]
5. Determine the critical points:
Solve [tex]\( (1 - x)(1 + x) = 0 \)[/tex]:
[tex]\[ 1 - x = 0 \quad \text{or} \quad 1 + x = 0 \][/tex]
This gives the critical points:
[tex]\[ x = 1 \quad \text{and} \quad x = -1 \][/tex]
6. Analyze the intervals defined by the critical points:
The critical points divide the number line into three intervals: [tex]\( (-\infty, -1) \)[/tex], [tex]\( (-1, 1) \)[/tex], and [tex]\( (1, \infty) \)[/tex].
Let's test a point from each interval to determine where the inequality holds:
- For [tex]\( x \in (-\infty, -1) \)[/tex], choose [tex]\( x = -2 \)[/tex]:
[tex]\[ (1 - (-2))(1 + (-2)) = (1 + 2)(1 - 2) = 3 \cdot (-1) = -3 \quad (\text{negative}) \][/tex]
- For [tex]\( x \in (-1, 1) \)[/tex], choose [tex]\( x = 0 \)[/tex]:
[tex]\[ (1 - 0)(1 + 0) = 1 \cdot 1 = 1 \quad (\text{positive}) \][/tex]
- For [tex]\( x \in (1, \infty) \)[/tex], choose [tex]\( x = 2 \)[/tex]:
[tex]\[ (1 - 2)(1 + 2) = (-1) \cdot 3 = -3 \quad (\text{negative}) \][/tex]
Also, check the critical points [tex]\(-1\)[/tex] and [tex]\(1\)[/tex]:
- At [tex]\( x = -1 \)[/tex]:
[tex]\[ (1 - (-1))(1 + (-1)) = (1 + 1)(1 - 1) = 2 \cdot 0 = 0 \quad (\text{zero, which is non-negative}) \][/tex]
- At [tex]\( x = 1 \)[/tex]:
[tex]\[ (1 - 1)(1 + 1) = 0 \cdot 2 = 0 \quad (\text{zero, which is non-negative}) \][/tex]
7. Conclusion:
Based on the test points, we find that the expression [tex]\((1 - x)(1 + x)\)[/tex] is non-negative on the interval [tex]\([-1, 1]\)[/tex].
Therefore, the solution set is:
[tex]\[ x \in [-1, 1] \][/tex]
Thus, the solution to the inequality [tex]\( x + 1 \geq x^2 + x \)[/tex] is:
[tex]\[ [-1, 1] \][/tex]
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Your search for answers ends at IDNLearn.com. Thanks for visiting, and we look forward to helping you again soon.